2017
DOI: 10.1002/adma.201702211
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Graphene Formation on Wood

Abstract: Wood as a renewable naturally occurring resource has been the focus of much research and commercial interests in applications ranging from building construction to chemicals production. Here, a facile approach is reported to transform wood into hierarchical porous graphene using CO laser scribing. Studies reveal that the crosslinked lignocellulose structure inherent in wood with higher lignin content is more favorable for the generation of high-quality graphene than wood with lower lignin content. Because of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
488
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(507 citation statements)
references
References 34 publications
15
488
0
4
Order By: Relevance
“…In addition to the I D / I G ratio, comparing the intensities of the G and 2D peaks can also provide key structural insights. The I G / I 2D ratio reaches the minimal of 1.79 at the laser power of 4.5%, which indicates that the CNS‐LSG was better structured, closer to the spectral signature of multilayered graphene . We thus conclude that to get good quality 3D graphene from CNS, the laser power should be set at the optimized laser power of 4.5%.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In addition to the I D / I G ratio, comparing the intensities of the G and 2D peaks can also provide key structural insights. The I G / I 2D ratio reaches the minimal of 1.79 at the laser power of 4.5%, which indicates that the CNS‐LSG was better structured, closer to the spectral signature of multilayered graphene . We thus conclude that to get good quality 3D graphene from CNS, the laser power should be set at the optimized laser power of 4.5%.…”
mentioning
confidence: 80%
“…There is great interest to develop simple, catalysis‐free and low‐temperature graphitization methods, such as electrochemical graphitization, and laser scribing graphitization . Laser scribing is a direct‐write method that can be used to convert graphene oxide, polyimide and many kinds of commercial polymers to porous graphene films which can be directly used as binder‐free electrodes for supercapacitors . Laser scribing preparation of graphene is a simple, catalyst‐free, eco‐friendly method, and shows great potential toward electronics and energy storage devices .…”
mentioning
confidence: 99%
“…Tour et al showed another example that commercial polyimide can be laser scribed into LSG by using a commercial CO 2 laser cutting machine ( Figure a) 225. Furthermore, they developed inert‐gas‐protected laser scribing and multiple laser scribing processes which enable the successful transformation from wood,226 cloth,227 bread into LSG (Figure 15b). Alshareef et al developed the LSG from natural lignin and used LSG as electrodes for high‐energy microsupercapacitors through a direct‐write lignin laser lithography technique 228.…”
Section: New Porogen Engineering Methodsmentioning
confidence: 99%
“…b) The formation of graphene can be done by laser scribing natural wood under inert‐atmosphere protection. Reproduced with permission 226. Copyright 2017, Wiley‐VCH.…”
Section: New Porogen Engineering Methodsmentioning
confidence: 99%
See 1 more Smart Citation